Impact of different intensities of intermittent theta burst stimulation on the cortical properties during TMS‐EEG and working memory performance. Issue 2 (9th November 2017) - Chung, Sung Wook; Rogasch, Nigel C.; Hoy, Kate E.; Sullivan, Caley M.; Cash, Robin F. H.; Fitzgerald, Paul B.
Abstract: Intermittent theta burst stimulation (iTBS) is a noninvasive brain stimulation technique capable of increasing cortical excitability beyond the stimulation period. Due to the rapid induction of modulatory effects, prefrontal application of iTBS is gaining popularity as a therapeutic tool for psychiatric disorders such as depression. In an attempt to increase efficacy, higher than conventional intensities are currently being applied. The assumption that this increases neuromodulatory may be mechanistically false for iTBS. This study examined the influence of intensity on the neurophysiological and behavioural effects of iTBS in the prefrontal cortex. Sixteen healthy participants received iTBS over prefrontal cortex at either 50, 75 or 100% resting motor threshold in separate sessions. Single‐pulse TMS and concurrent electroencephalography (EEG) was used to assess changes in cortical reactivity measured as TMS‐evoked potentials and oscillations. The n‐back task was used to assess changes in working memory performance. The data can be summarised as an inverse U‐shape relationship between intensity and iTBS plastic effects, where 75% iTBS yielded the largest neurophysiological changes. Improvement in reaction time in the 3‐back task was supported by the change in alpha power, however, comparison between conditions revealed no significant differences. The assumption that higher intensity results in greater neuromodulatory effects may be false, at least in healthy individuals, and should be carefully considered for clinical populations. Neurophysiological changes associated with working memory following iTBS suggest functional relevance. However, the effects of different intensities on behavioural performance remain elusive in the present healthy sample.